Methodological considerations for and validation of the ultrasonographic determination of human skeletal muscle hypertrophy and atrophy - Stokes, Tanner; Tripp, Thomas R.; Murphy, Kevin; Morton, Robert W.; Oikawa, Sara Y.; Lam Choi, Hon; McGrath, Jessica; McGlory, Chris; MacDonald, Maureen J.; Phillips, Stuart M. (Physiological reports, 2021)
Magnetic resonance imaging (MRI) is the current gold standard for measuring changes in muscle size (cross‐sectional area [CSA] and volume) but can be cost‐prohibitive and resource‐intensive. We evaluated the validity of B‐mode ultrasonography (US) as a low‐cost alternative to MRI for measuring muscle hypertrophy and atrophy in response to resistance training and immobilization, respectively. Fourteen young men performed 10wk of unilateral resistance training (RT) to induce muscle hypertrophy. In the final two weeks of the 10wk, the subjects’ contralateral leg was immobilized (IMB). The cross‐sectional area of the vastus lateralis (VLCSA) was measured at the mid‐thigh before and after each intervention using MRI (VLCSAMRI) and US (VLCSAUS). The relationship and agreement between methods were assessed. Reliability of US measurements ranged from good to excellent in all comparisons (ICC >0.67). VLCSA significantly increased after 10 weeks of RT (VLCSAUS: 7.9 ± 3.8%; VLCSAMRI: 7.8 ± 4.5%) and decreased after 2 weeks of IMB (VLCSAUS: −8.2%±5.8%; VLCSAMRI: −8.7 ± 6.1%). Significant correlations were identified between MRI and US at each time point measured (all r > 0.85) and, importantly, between MRI‐ and US‐derived changes in VLCSA. Bland‐Altman analysis revealed minimal bias in US measurements relative to the MRI (−0.5 ± 3.0%) and all measurements were within the upper and lower limits of agreement. Our data suggest that B‐mode ultrasonography can be a suitable alternative to MRI for measuring changes in muscle size in response to increased and decreased muscle loading in young men. We demonstrate that ultrasound‐derived measurements of vastus lateralis hypertrophy and atrophy induced by resistance training and immobilization are significantly correlated with MRI‐derived measurements. The reliability of our ultrasound technique was also in the range of good‐excellent. Together, these data suggest that B‐mode ultrasonography is a suitable alternative for the assessment of muscle hypertrophy and atrophy under conditions of dynamic loading in young men.